Overview of the Active Ingredients in Cosmetic Products for the Care of Skin That Has Been Exposed to Ionizing Radiation – Analysis of Their Effectiveness in Breast Cancer Radiotherapy - Kondziołka J; Wilczyński S (Dove Medical Press, 2021)
Joanna Kondziołka, Sławomir Wilczyński Department of Basic Biomedical Science, Faculty of Pharmaceutical Sciences in Sosnowiec, Medical University of Silesia, Katowice, PolandCorrespondence: Sławomir Wilczyński Email kpnb@sum.edu.plAbstract: Treatment that uses ionizing radiation is one of the most common therapeutic methods in case of breast cancer. However, it often results in radiation dermatitis, which manifests itself, among others, as erythema, burning, itching and pain as well as dry or moist desquamation of the epidermis in the irradiated areas. The intensity of these symptoms significantly reduces the patient's quality of life, which could affect the effectiveness of the entire therapy. There are more and more cosmetic preparations on the market for daily care of skin that has been exposed to radiation. The composition of the active ingredients in these preparations is designed to support the protective functions of the skin, delay the occurrence of the side effects of ionizing radiation, reduce their intensity, and accelerate the regeneration of the irradiated areas. Unfortunately, there is little scientific evidence of the effectiveness of the active ingredients that are contained in these preparations. This paper presents a narrative review of the most commonly used ingredients and compares them with the current state of knowledge on their effectiveness in preventing radiodermatitis.Keywords: active substances, breast cancer, prevention, radiation dermatitis, radiotherapy